DEVELOPMENT OF AUGMENTED REALITY-BASED PHYSICS MODULE ON CIRCULAR MOTION - Annisa Nur Latifah; Faizatul Mabruroh; Suhadi Suhadi; Tasya Afrizah (Physics and Science Education Journal (PSEJ), 2025)
This study aims to develop a valid and practical augmented reality-based physics module on circular motion material used in learning. The background of this study is the difficulty of students in understanding the concept of circular motion and the minimal use of technology-based teaching materials such as augmented reality in schools. This study uses the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, and Disseminate), but is only carried out up to the Develop stage. The subjects of the study were 2 physics teachers and 15 students of class XI IPA SMA Azharyah Palembang. Data collection techniques include observation, interviews, and questionnaires, while data analysis techniques use a Likert scale to assess the validity and practicality of the product. The validation value was obtained from the validation results by material, media, and language experts with an average percentage value of 81.67% which indicates that the developed module is in the very valid category. The practicality value is obtained from the responses of teachers and students after using the augmented reality-based physics module on the circular motion material in a small-scale trial obtained a percentage of 88.5% with very practical criteria and in the practicality test the teacher obtained a percentage of 88% with very practical criteria. Thus, this augmented reality-based physics module is suitable for use as an interactive learning media to improve students' understanding of the circular motion material.